Pengaruh Customer Experience dan Harga Terhadap Minat Beli Pengguna Shopee - Syara Dwi Afiana; Ridwansyah; Muhammad Iqbal Fasa (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to analyze the influence of two crucial elements, namely Customer Experience and Price, on the purchasing decisions of Shopee users. Information technology and digital transformation have altered the way consumers interact with the market. E-commerce platforms have become the main foundation for this change, with Shopee as a key player illustrating this significant shift. The dramatic change in consumer behavior from conventional shopping to online shopping raises important questions about how customers interact with e-commerce platforms. Shopee, as an entity reflecting this dynamic, becomes the focus of research to understand the impact of Customer Experience and Price on consumer purchasing interest. The research method employed is quantitative, using multiple linear regression analysis. The study's findings indicate that Customer Experience and Price have a positive and significant influence on the purchasing interest of Shopee consumers.